JAN LOKPAL MOVEMENT: A REVIEW OF THE ANTI-CORRUPTION MOVEMENT IN INDIA - Gaikwad, Ravi Sahebrao; Shende, Dattu Dadasaheb (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Jan Lokpal Movement has to be seen as a significant socio-political event in India. The Jan Lokpal Movement emerged as an important stage in the anti-corruption movement in India. The Jan Lokpal Movement, which emerged in 2011, was led by social activist Anna Hazare. The movement demanded the establishment of an independent Lokpal with the power to investigate and prosecute cases of corruption of public administrative officials. This research paper reviews the Jan Lokpal Movement and explores the origin, development and impact of this movement on the political landscape of India. This research paper analyses the strengths and weaknesses of the Jan Lokpal Movement. At the same time, this paper attempts to understand the active dynamics of the anti-corruption movement in India and its impact on governance and civil society.